PRIORITIES AND MECHANISMS OF MODERNIZING STRATEGIES OF THE MILITARY INDUSTRIAL COMPLEX OF NATO COUNTRIES IN VIEW OF UKRAINE’S WAR WITH RUSSIA - Kudyrko, L. P.; Andriiets, B. V. (The actual problems of regional economy development, 2024)
This article is devoted to determining the priorities and mechanisms of modernization of the military-industrial complex strategies of NATO countries, taking into account new geopolitical challenges. Russian aggression against Ukraine demonstrated new threats to Euro-Atlantic security, which led to the need for the states of the North Atlantic Alliance to find mechanisms to strengthen their ability to respond to these challenges. The purpose of this article is to reveal the priorities and mechanisms for the modernization of the MIC strategies of NATO countries in the conditions of modern geopolitical challenges. A complex of methods was used to study this issue, namely: analysis and synthesis, empirical and statistical analysis; comparative analysis; systematization. On the basis of the data of international organizations, the vectors of development and modernization of the military-industrial complex of NATO countries have been identified, taking into account the peculiarities of the war between Russia and Ukraine. The results of the study reveal the content and specifics of the implementation of the new «Build Allied» strategy, which is aimed at strengthening and ensuring a more powerful industrial base of the North Atlantic Alliance. It was determined that the mechanism for the development and deepening of international strategic partnerships is a tool for the implementation of this ambitious task. Industrial and technological collaboration of partners in the field of modern weapons production will create prerequisites for the formation of flexible and efficient production and sales systems, adaptable to both current and future global challenges. It was determined that quantum technologies can become a special direction of prospective cooperation. They are able to make a unique contribution to the development of the fields of computing and communication. These new technological and management capabilities are determined by the fact that in modern conditions there are no close analogues outside the Alliance, which can become a significant strategic advantage. The theoretical significance of the study lies in the expansion of knowledge about the current state of the military-industrial complex of NATO countries, highlighting its strengths and weaknesses, opportunities and threats that it faces in the context of the war in Ukraine. The systematization and disclosure of existing and proposed mechanisms for the modernization of MIC strategies can serve as a basis for further analysis of the influence of external factors on the modernization processes in the strategic sectors of the economy of the Alliance states. The practical value is determined by the search for new regulatory mechanisms to strengthen NATO’s position in the international arena considering to the aggravation of geopolitical rivalry in the context of the war between Ukraine and the Russian Federation. Prospects for further research can be seen in the determination of effective strategies for the development of the domestic military-industrial complex, mechanisms for the integration of domestic enterprises into international production and distribution networks of military products with the participation of NATO member states, which is one of the key factors in Ukraine’s victory in the war with the Russian Federation.